How can educational innovations become sustainable? A review of the empirical literature - Prenger, R.; Tappel, A. P. M.; Poortman, C. L.; Schildkamp, K. (Frontiers in Education, 2022)
In literature there is a great variety in the definitions and identified critical features of sustainability of educational innovations. The aim of this review is to provide an overview of the entire range of factors influencing the sustainability and its core aspects. A systematic review was performed in which electronic databases were searched for peer reviewed articles, published between 2002 and 2017. Based on results of 44 publications, the following definition could be constructed: ‘Sustainability refers to the process of integrating the intervention’s core aspects in organizational routines, which are adaptive to ongoing work, with maintenance or continuation of improved results’. We found four main factors influencing sustainability of educational innovations: school organizational, innovation, individual, and context characteristics. The empirical-based model developed in this review should be validated in practice to create transparency and focus in sustainability research.